Combination Carbon Nanotubes with Graphene Modified Natural Graphite and Its Electrochemical Performance - DENG Ling-feng; PENG Hui-yan; QIN Yu-kun; WU Yi-qiang (Cailiao gongcheng, 2017)
The CNTs/rGO/NG composite lithiumion battery anode material was synthesized by thermal reducing, using graphene oxide (GO) and carbon nanotubes (CNTs) as precursors for a 5 ∶ 3 proportion. The morphology, structure, and electrochemical performance of the composite were characterized by scanning electron microscopy(SEM), X-ray diffractometry(XRD), Fourier transform infrared spectra (FTIR) and electrochemical measurements. The results show that reduced graphene oxide and carbon nanotubes form a perfect three-dimensional network structure on the surface of natural graphite. CNTs/rGO/NG composite has good rate performance and cycle life,compared with pure natural graphite.The initial discharge capacity of designed anode is 479mAh/g at 0.1C, the reversible capacity up to 473mAh/g after 100 cycles,the capacity is still 439.5mAh/g, the capacity retention rate is 92%,and the capacity is 457, 433, 394mAh/g at 0.5, 1, 5C, respectively.